Impact of high-pressure processing on the stability and bioaccessibility of bioactive compounds in Clementine mandarin juice and its cytoprotective effect on Caco-2 cells. Issue 10 (1st October 2020) - Cilla, Antonio; Rodrigo, María J.; De Ancos, Begoña; Sánchez-Moreno, Concepción; Cano, M. Pilar; Zacarías, Lorenzo; Barberá, Reyes; Alegría, Amparo
Abstract : HPP can be recommended as a suitable technology to retain or indeed increase antioxidant bioactives and their cytoprotective activity in Clementine mandarin juices after gastrointestinal digestion. Abstract : Mandarin juice is a rich source of antioxidant bioactive compounds. While the content and profile of bioactives are known, the impact of high-pressure processing (HPP) on their stability and bioaccessibility (BA) is unknown, but may allow obtaining safe, nutritious, and fresh-tasting juices with highly extractable bioactive compounds. The stability and BA of bioactive antioxidant compounds in untreated and HPP-treated (400 MPa/40 °C/1 min) Clementine mandarin juices, and the cytoprotective effect of its bioaccessible fractions (BF) obtained after simulated gastrointestinal digestion against H2 O2 -induced oxidative stress in differentiated Caco-2 cells were investigated. The BF of HPP-treated juices showed a better retention of carotenoids, flavonoids, ascorbic acid, total polyphenols and FRAP value, and slightly higher cytoprotection (mitochondrial membrane potential and ROS) than untreated juices. Therefore, HPP can be recommended as a suitable technology to retain or indeed increase antioxidant bioactives and their cytoprotective activity in mandarin juices after gastrointestinal digestion.